1965
DOI: 10.1111/j.1365-2621.1965.tb00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Evaluation of the Saccharide Components of Starch Hydrolysates. II. Evaluation

Abstract: Oligosaccharidesof DP 3-10 were evaluated for their properties of density, refraetive index, viscosity, optical rotation, reducing power, and infrared absorption characteristics.Tables of data were developed giving the expected values of each property for each oligosaecharide.As expected, density, refractive index, viscosity, optical rotation, and reducing power were related to the molecular weight of the sugars. The degree of the effect of molecular weight on each of these properties was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Thus DE is a theoretically predictable parameter in acid hydrolysed corn syrups, in which the percentages of the component saccharides from n = 1 to n = 7 are known. Hoover et al (1965) have found disagreement between the reducing power, based on ferricyanide number, of maltodextrins and DE presumably calculated on the same basis. I t should be pointed out, however, that reduction of the ferricyanide ion by sugars is not only non-stoicheiometric with respect to copper salts but highly complex in mechanism.…”
Section: Figmentioning
confidence: 89%
“…Thus DE is a theoretically predictable parameter in acid hydrolysed corn syrups, in which the percentages of the component saccharides from n = 1 to n = 7 are known. Hoover et al (1965) have found disagreement between the reducing power, based on ferricyanide number, of maltodextrins and DE presumably calculated on the same basis. I t should be pointed out, however, that reduction of the ferricyanide ion by sugars is not only non-stoicheiometric with respect to copper salts but highly complex in mechanism.…”
Section: Figmentioning
confidence: 89%
“…A cauchy dispersion layer was used to determine the thickness of the APTES, maltoheptaose, and polysaccharide layer. A refractive index of 1.336 28 was used for maltoheptaose and the α-glucan brush and a refractive index of 1.465 for APTES.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%